Achieving high-performance non-halogenated nonfullerene acceptor-based organic solar cells with 13.7% efficiency via a synergistic strategy of an indacenodithieno[3, 2-b]selenophene core unit and non-halogenated thiophene-based terminal group. Issue 42 (9th October 2019) - Liu, Kai-Kai; Xu, Xiaopeng; Wang, Jin-Liang; Zhang, Chao; Ge, Gao-Yang; Zhuang, Fang-Dong; Zhang, Han-Jian; Yang, Can; Peng, Qiang; Pei, Jian
Abstract : The combination of indacenodithieno[3, 2- b ]selenophene core unit and thiophene-containing IC is a successful synergistic strategy with PCE of 13.7%, which is the highest value in NFAs with thiophene-containing IC for binary OSCs. Abstract : An outmost selenophene-functionalized electron-rich central core (indacenodithieno[3, 2- b ]selenophene) and a new non-halogenated A–D–A architecture non-fullerene small molecular acceptor (NF-SMA) (TSeTIC ) based on indacenodithieno[3, 2- b ]selenophene as the central unit and thiophene-fused IC as a terminal group was designed and synthesized for high performance organic solar cells. In contrast to the similar NF-SMA (TTTIC ) with an indacenodithieno[3, 2- b ]thiophene unit, TSeTIC exhibited a stronger and red-shifted absorption spectrum, higher highest occupied molecular orbital (HOMO) energy level, and enhanced electron mobility in neat thin films. Furthermore, a TSeTIC /PM6 -based device presented higher hole/electron mobility, better phase separation features with favorable morphology, and higher charge dissociation and collection efficiency than a TTTIC /PM6 -based device, resulting in remarkably improved J sc and FF without sacrificing the V oc . Therefore, compared to the best PCE of 12.05% with an energy loss ( E loss ) of 0.64 eV for the PM6 /TTTIC device, the optimized PM6 /TSeTIC device yields a significantly higher PCE of 13.71% with a higher FF of 75.9% and decreased E loss of 0.60 eV. It is worth noting that the excellent PCE of 13.71% is the highest recorded for A–D–A structural NF-SMAs with thiophene-containing terminal groups for binary organic solar cells. These results demonstrate that the synergistic strategy of using an indacenodithieno[3, 2- b ]selenophene core unit and thiophene-containing IC end group is a promising avenue to enhance the PCE of non-halogenated NF-SMAs with high V oc and FF as well as low E loss .